THE ROLE OF KKN IN TRANSFORMING THE FUNCTION OF MOSQUES: FROM A PLACE OF WORSHIP TO A CENTER FOR CHILDREN'S ACADEMIC DEVELOPMENT - Alia Mifta Hunni’mah; Diana Lorenza; Prahasini Prahasini; Adrian Maulana Ibrahim; Deni Karisma; Rodiyah Rodiyah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Actually, mosques aren’t just places for worship; they also act as centers for education, social training, and community development. But these days, mosques are often mainly used for ritual worship. This article looks at how the Community Service Program (KKN) strategy helps turn mosques into spaces for kids’ academic growth. The study uses a qualitative descriptive method with data collected through observation and documents during the KKN. Data analysis involved reducing, presenting, and drawing conclusions from the data. The findings show that the KKN program encourages new ways of using mosques, like tutoring, homework help, literacy programs, and other educational activities with kids. The program positively impacts motivation to learn, reading ha bits, discipline, and helps shape kids’ religious character. The success of this transformation.